Automation and demographic change - Ana Abeliansky; Klaus Prettner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
We analyze the effects of declining population growth on the adoption of automation technology. A standard theoretical framework of the accumulation of traditional physical capital and of automation capital predicts that countries with a lower population growth rate are the ones that innovate and/or adopt new automation technologies faster. We test the theoretical prediction by means of panel data for 60 countries over the time span from 1993 to 2013. Regression estimates provide empirical support for the theoretical prediction and suggest that a 1% increase in population growth is associated with approximately a 2% reduction in the growth rate of robot density. Our results are robust to the inclusion of standard control variables, the use of different estimation methods, the consideration of a dynamic framework with the lagged dependent variable as regressor, and changing the measurement of the stock of robots.
urn:nbn:de:bsz:100-opus-13363
Keywords: J11; O14; O33; O40; 330; Automation; Industrial Robots; Demographic Change; Declining Population Growth; Economic Growth